Effect of indomethacin on the incidence of experimental Escherichia coli pyelonephritis. - Glauser, M P (1983)
In the presence of temporary obstruction (20 h), ascending Escherichia coli urinary infection leads to irreversible acute exudative pyelonephritis (AEP) in rats. The purpose of the present study was to investigate the early inflammatory events which take place in response to the presence of bacteria in the kidney parenchyma and lead to the development of AEP. Rats were given indomethacin before and during the obstructive phase of kidney infection and were sacrificed at different times thereafter. Although renal infection (as defined by bacterial counts) was equally frequent (76%) and severe in indomethacin-treated and control rats sacrificed at the end of the obstructive period, it was found that the incidence of AEP (as defined by the inflammatory response of the kidney elicited by bacteria) 2 days after removal of the obstruction was significantly reduced from 74% in controls given water to 48% in indomethacin-treated animals (P = 0.02). Rat kidneys without AEP had bacterial counts of 10(2)/g. Since indomethacin apparently had no direct antibacterial activity against E. coli and no effect on urine osmolalities, it is likely that the reduction in the incidence of AEP and the concomitant eradication of bacteria after removal of the obstruction was due to an effect of indomethacin that is related to the renal response to infection. This was possibly due to decreased inflammation, as indicated by the fact that when pyelonephritis developed in indomethacin-treated rats it was less severe than in controls. These results suggest that if inflammation can be mitigated when bacteria are present in the kidney during obstruction, the bacteria may be cleared spontaneously once the normal urinary flow is restored.